THE EFFECTIVENESS OF FUN LEARNING IN IMPROVING THE COMPREHENSION OF EFFECTIVE SENTENCES OF ELEMENTARY SCHOOL STUDENTS: EFEKTIVITAS FUN LEARNING DALAM MENINGKATKAN PEMAHAMAN KALIMAT EFEKTIF SISWA SD - Zikri Darmawan; Latif (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research is motivated by the low ability of students to understand and compose effective sentences due to the application of conventional learning methods that tend to be boring and less interactive. The purpose of this study is to determine the effectiveness of the application of the Fun Learning method in improving the understanding of effective sentences of grade IV students of SD Negeri 113 Pekanbaru. The research uses a quantitative approach with a pre-experimental design of the one group pretest-posttest design. The research subjects consisted of 26 students of class IV A who were selected through purposive sampling techniques. The research instrument is in the form of pretest and posttest tests that measure the ability to understand the elements of effective sentences. The data were analyzed using the Paired Sample t-test with the help of the SPSS version 25 program. The results showed a significant improvement in students' abilities after the implementation of the Fun Learning method, with an average pretest score of 51.92 increasing to 87.58 in the posttest. The significance value (Sig. 2-tailed) = 0.000 < 0.05 proves that there is a significant influence between the application of the Fun Learning method on students' effective sentence comprehension. Qualitatively, the application of Fun Learning creates an active, interactive, and fun learning atmosphere, thereby increasing student motivation, participation, and confidence. The implications of this study show that the Fun Learning method is effectively applied in Indonesian learning in elementary schools, especially in effective sentence materials. Teachers are advised to integrate this approach in the learning process to improve the quality of language understanding and form positive character of students.